Spatial distribution of structural lineaments in the Al-Lith geothermal field, western Saudi Arabia: Remote sensing and aeromagnetic data analysis - Jawad Rafiq; Israa S. Abu-Mahfouz; Konstantinos Chavanidis; Daffa Arrofi; Pantelis Soupios (Journal of Asian Earth Sciences: X)
Saudi Arabia is enriched in numerous geothermal resources. Among these, Wadi Al-Lith is regarded as one of the favorable geothermal prospects in western Saudi Arabia, featuring several hot springs with a discharge temperature of around 95 °C. However, there is still uncertainty regarding the delineation of the prospective geothermal reservoir, and the assessment of the geothermal energy reserves. Therefore, this paper aims to delineate the prospective geothermal area, utilizing remote sensing and geophysical (magnetic) data. This research maps the surface and subsurface geological and structural features (faults, fractures, and fold axes) and analyzes their densities using an integrated geological-remote sensing-geophysical investigation. Digital elevation models and Landsat-8 imagery, supported by field investigations, were used to analyze surface lineament density, while airborne magnetic data was used to analyze subsurface lineament density. The study area was subdivided into ten zones based on surface lineament density, with the northernmost zone presenting the highest lineament density. Subsurface lineament density analysis revealed five high-density zones, three of which correspond well with those identified on the surface. The study also identified the main high-permeability zones and associated geothermal anomalies in the Wadi Al-Lith area, improving the understanding of its potential geothermal resources. The results of this study could serve as a preliminary guide for further geothermal exploration, highlighting surface manifestations that require in-depth investigation using geoscientific and drilling tools.